Maternal iron status in pregnancy and child health outcomes after birth: a systematic review and meta-analysis - Quezada-Pinedo, Hugo G.; Cassel, Florian; Duijts, Liesbeth; Muckenthaler, Martina; Gassmann, Max; Jaddoe, Vincent W. V.; Reiss, Irwin K. M.; Vermeulen, Marijn J. (Nutrients, 2021)
In pregnancy, iron deficiency and iron overload increase the risk for adverse pregnancy outcomes, but the effects of maternal iron status on long-term child health are poorly understood. The aim of the study was to systematically review and analyze the literature on maternal iron status in pregnancy and long-term outcomes in the offspring after birth. We report a systematic review on maternal iron status during pregnancy in relation to child health outcomes after birth, from database inception until 21 January 2021, with methodological quality rating (Newcastle-Ottawa tool) and random-effect meta-analysis. (PROSPERO, CRD42020162202). The search identified 8139 studies, of which 44 were included, describing 12,7849 mother-child pairs. Heterogeneity amongst the studies was strong. Methodological quality was predominantly moderate to high. Iron status was measured usually late in pregnancy. The majority of studies compared categories based on maternal ferritin, however, definitions of iron deficiency differed across studies. The follow-up period was predominantly limited to infancy. Fifteen studies reported outcomes on child iron status or hemoglobin, 20 on neurodevelopmental outcomes, and the remainder on a variety of other outcomes. In half of the studies, low maternal iron status or iron deficiency was associated with adverse outcomes in children. Meta-analyses showed an association of maternal ferritin with child soluble transferrin receptor concentrations, though child ferritin, transferrin saturation, or hemoglobin values showed no consistent association. Studies on maternal iron status above normal, or iron excess, suggest deleterious effects on infant growth, cognition, and childhood Type 1 diabetes. Maternal iron status in pregnancy was not consistently associated with child iron status after birth. The very heterogeneous set of studies suggests detrimental effects of iron deficiency, and possibly also of overload, on other outcomes including child neurodevelopment. Studies are needed to determine clinically meaningful definitions of iron deficiency and overload in pregnancy.
Gesehen am 13.10.2021